Stem and leaf anatomical studies of selected species of barlerieae and ruellieae (acanthaceae) from Yemen - Anisa S. Al-Hakimi,; Sarah Abdul Razak,; N. Omar,; Abdulwahab A. Saeed,; Shamsul Khamis,; A. Latiff, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The anatomy of stems and leaves of selected species of tribes Barlerieae and Ruellieae (Acanthaceae) was studied to assess the taxonomic significance of anatomical characteristics in the two tribes. The anatomical characters such as the outline of stems, midribs, petioles, margins, shape of epidermal cells, vascular bundles, stomata, anticlinal cells, cystoliths, aerenchyma cells, layer of wax, layer of hypodermis were observed and analysed. Type of trichomes observed on the leaf surface using Scanning Electron Microscopy and light microscope provides information of taxonomic significance to both tribes and the taxa within them. The trichomes vary from non-glandular (unicellular, bicellular, multicellular, and multiradiate) to capitate glandular. Abundance of long-stalked trichomes was recorded only in Neuracanthus aculeatus. Cystoliths of different size and position are present in epidermis, parenchyma and collenchyma in addition to oil cells in some genera. The placement of Neuracanthus among the recognized tribes of Acanthaceae is assessed using anatomical characters.